RIFT IN THE EUROPEAN UNION’S PERFECT GOVERNANCE CYCLE OF GREEN DEAL DIPLOMACY IN THE WESTERN BALKANS - Stefanović-Štambuk, Jelica (Political Review, 2024)
The two significant failures of the European Green Deal diplomacy undermine the success of sustainable development efforts to mitigate the effects of climate change, as well as the enlargement process of all of the European Union's enlargement partners in the Western Balkans. This study inquires into the efficacy of European Green Deal diplomacy in the region. Although the European Union regularly presents itself as a global leader in sustainability, there is a discrepancy between its goals and aspirations and its actual accomplishments. The 2009 Lisbon Treaty improved the European Union's diplomacy’s intra-cohesiveness and diplomatic apparatus. In terms of effectiveness, the European Green Deal diplomacy has fallen short. The European Green Deal could not address climate, environmental, and biosocial unsustainability by successfully balancing nature's rights with human prosperity and the economies that support it. However, data from the Western Balkans shows that the EU has not successfully addressed issues in this region by employing European Green Deal diplomacy. Notable deficiencies have resulted from a lack of effort to respect, legalize, and uphold the rights of nature, as well as assist regional decarbonization. While the EU rhetorically celebrates its sustainability and climate action achievements, the concrete steps taken in regionally implemented European Green Deal diplomacy reveal a lack of economic and environmental reconciliation. Additionally, the European Union increasingly uses European Green Deal diplomacy in the region to achieve its geopolitical competitive goals. The study comes to the conclusion that to achieve sustainability goals effectively; the European Union must concentrate on incorporating nature's rights and sustainable practices into its European Green Deal policy and diplomacy framework. The theoretical-methodological approach is based on a critical analysis of prior research in the literature on European Green Deal diplomacy, global politics on sustainable development, and the issues surrounding the “triple planetary crisis.” We examined the development of the European Union's sectoral diplomacy process from 2016 to the conduct of the European Green Deal's unifying diplomacy in the Western Balkans since 2019, employing relational diplomatic analysis from the perspective of the interdisciplinary sustainability paradigm. The apparent conflicts in the relationship's transformation towards sustainable development stem from the systemic and managerial imbalances of the three elements of sustainable development in the EU’s diplomacy and policy. According to the findings, the European Green Deal's lack of a foundation in the rights of nature and its growing emphasis on accomplishing the specific geopolitical objectives of the European Union in the Western Balkans are the leading causes of its diplomatic shortcomings in the region. To exit the global regime of unsustainability by achieving the Sustainable Development Goals by 2030 and climate neutrality by 2050, it is concluded that strong democratic initiatives by the people of the Western Balkans for sustainable development to benefit nature and the realization of the human right to a clean, healthy, safe, and sustainable environment can be an essential incentive to change the diplomacy of the European Green Deal towards a basis of true reconciliation with nature.
Keywords: Rights of Nature; Diplomacy; European Union; Western Balkans; European Green Deal; European Commission; Sustainable Development Goals; Climate Change; critical raw materials; Berlin Process